Efecto de la fertilización en la producción de materia seca y extracción de nutrientes en tres accesiones de lippia origanoides h.b.k. (2012)
An experiment under greenhouse conditions at the Universidad Nacional de Colombia- Palmira to evaluate the relationship among plant nutrition, levels of nutrient uptake and dry matter production of three accessions of Lippia origanoides (Patía, Cítrica and Típica), was carried out. Concentrations of foliar nutrients, absorption and extraction rates (of 5 elements N, P, K, Mg and Ca) and their relationship with the production of each accession were evaluated. A split plot design with 11 treatments and three replications was used. The experimental units consisted of a plant sowed in substrate (peat). Fertilization was done by fertigation using the modified Hoagland and Arnon nutrient solution. The Patía accession showed the maximum dry matter yield (292.0 ± 0.1 g plant-1) with the treatment 8 (Mg decreased), the Cítrica accession yielded 287.1 ± 0.1 g plant-1 with the treatment 9 (Mg increase) and finally Típica accession (255.2 ± 0.1 g plant-1) with the treatment 8. In terms of absorption of nutrients, potassium is the most required element (13.9 kg t-1), followed by calcium (7.9 kg t-1).